The Eighth Mahler and the world in 1910 - Johnson, Stephen 1955- (The University of Chicago Press, 2020)
"The world premiere of Gustav Mahler's Eighth Symphony in Munich in 1910 was the artistic breakthrough for which the composer had yearned all his life, filling Munich's huge Neue Musik-Festhalle on two successive evenings to rapturous and tumultuous applause. Representatives of many European royal houses were in attendance, along with luminaries of literary and musical world. Also in attendance were Alma Mahler, the composer's young wife, and Alma's longtime lover, the architect Walter Gropius. Knowledge of their relationship would precipitate an emotional crisis in Mahler that, compounded with his heart condition and the death of his young daughter Maria, would lead to his premature death the next year, in 1911. In The Eighth, Stephen Johnson provides a masterful account of the symphony's far-reaching effect on composers, conductors, and writers of the time -- Berg and Schoenberg, the teenage Korngold, Bruno Walter and Klemperer, and Zweig and Mann. Johnson's story of the masterpiece and of the fate of the man who created it makes for absorbing reading and will be a must-read for classical music lovers"--
Keywords: Mahler, Gustav -- 1860-1911 -- Sinfonien -- Nr. 8; Geschichte 1910; Uraufführung; München; Mahler, Gustav / 1860-1911; Mahler, Gustav / 1860-1911 / Symphonies / no. 8 / E♭ major; Mahler, Gustav / 1860-1911 / Appreciation; Mahler, Gustav / 1860-1911 / Family; Mahler, Alma / 1879-1964; Music / First performances / Germany / Munich; Composers / Austria; Jewish composers / Austria; Symphonies (Mahler, Gustav); Art appreciation; Composers; Families; Jewish composers; Music / First performances; Austria; Germany / Munich